THE EFFECT OF CASE-BASED LEARNING WITH AUGMENTED REALITY ON BIOLOGY LEARNING OUTCOMES AND CRITICAL THINKING AT SMAN 14 SAMARINDA - Zamima, Raysa; Herliani, Herliani; Rambitan, Vandalita Maria Magdalena; Nasution, Ruqoyyah (Universitas Bhinneka PGRI, 2025)
This study aims to determine the effect of case-based learning model with augmented reality media on cognitive learning outcomes and critical thinking skills in biology learning material on environmental change and preservation of class X students of SMAN 14 Samarinda. The research method used was quasi experimental design in the form of non-equivalent control group with a total sample of 54 students from 2 different classes. Data analysis techniques using N-Gain test and independent sample t-test. The results of data analysis showed that on learning outcomes with the N-Gain test the control class had an average of 0.45 with a moderate category and the experimental class with an average of 0.61 with a moderate category. The results of the independent sample t-test test showed a sig value. (2-tailed) 0.001 for critical thinking skills, the value is smaller than 0.05 so it can be concluded that there is an effect of the case-based learning model with augmented reality media on learning outcomes and critical thinking skills in biology learning material on environmental change and preservation of class X students of SMAN 14 Samarinda.